Red Sea rifting in central Egypt: constraints from the offshore Quseir province. Issue 2 (2023) - Ali, Moamen; Decarlis, Alessandro; Ligi, Marco; Ball, Philip; Ceriani, William Bosworth and Andrea
No abstract available